Distribution Patterns and Habitat of Mammals in Mandalawangi Resort of Mount Gede Pangrango National Park - Tun Susdiyanti; Ken Dara Cita; Annisa Izzatin Widawardani Kusno (Indonesian Journal of Applied Research (IJAR), 2020)
Distribution pattern and habitat quality of mammals is essential to keep the existing of mammals which depends on interactions between its intrinsic evolutionary and ecological system. Mandalawangi Resort aside from being a conservation area, it is also a tourist area. Tourism activities carried out in the region, will directly and indirectly affect the sustainability of mammal diversity. The benefits of mammals are to stabilize the food chain, the spread of plant seeds, as an object of research and education. The study aims to determine the distribution patterns and habitat of mammals in Mandalawangi Resort . Research on mammal diversity was carried out using 4 methods: rapid assessment, line transect, animal footprint. Habitat data obtained using vegetation analysis and field observation methods. The diversity of mammals in the Mandawalangi Resort consists of 7 types of mammals from 6 families, namely kekes squirrel (Tupaia javanica), langur (Trachypithecus auratus), wild cats (Felis domesticus), wild boar (Sus scrofa), leopard (Panthera pardus melas) , civet mongoose (Paradoxurus hermaphroditus) and house gutters (Suncus murinus). Species wealth index is low (0.50). The diversity index of mammals is included in the low diversity category (0.25). The highest level of mammal species meeting is kekes squirrel (Tupaia javanica) with a value of 29.4%. Evenness index is included in the unstable community category (0.15). Mammalian habitat is divided into tropical rain forests and open land with dominating trees namely Damar (Agathis damara) and Rasamala (Altingia excelsa).